Blood pressure control in diabetic kidney disease: a post-hoc analysis of the FANTASTIC trial - Cheol Ho Park; Soon Jun Hong; Sung Gyun Kim; Seok Joon Shin; Dong Ki Kim; Jung Pyo Lee; Sang Youb Han; Sangho Lee; Jong Chul Won; Young Sun Kang; Jongha Park; Byoung-Geun Han; et al. (BMC, 2024)
Abstract Background The target blood pressure (BP) value is unclear for diabetic kidney disease (DKD). Therefore, we aimed to evaluate the effect of strict BP control or 'on treatment' BP on clinical outcomes in patients with DKD. Methods A post-hoc analysis of the prespecified secondary outcomes of the FimAsartaN proTeinuriA SusTaIned reduCtion in comparison with losartan in diabetic chronic kidney disease (FANTASTIC) trial, a randomized multicenter double-blind phase III trial. Eligible patients were aged ≥ 19 years with DKD. We assigned 341 participants with DKD to BP control strategy (standard-systolic BP [SBP] < 140 mmHg versus strict-SBP < 130 mmHg). The outcome was the occurrence of cardiovascular events and renal events. Separate analyses were performed to compared the risk of outcome according to achieved average BP levels. Results A total of 341 participants were included in the analysis. Over a median follow-up of 2.8 years, cardiovascular/renal events were observed in 25 (7.3%) participants. Mean (SD) SBPs in the standard and strict BP control group were 140.2 (11.6) and 140.2 (11.9) mmHg, respectively. The strict BP control group did not show significantly reduced risk of cardiovascular/renal events (HR 1.32; 95% CI 0.60-2.92]). In the post-hoc analyses using achieved BP, achieved average SBP of 130-139 mmHg resulted in reduced risk of cardiovascular/renal events (HR 0.15; 95% CI 0.03-0.67) compared to achieved average SBP ≥ 140 mmHg, whereas further reduction in achieved average SBP < 130 mmHg did not impart additional benefits. Conclusion In patients with DKD, targeting a SBP of less than 130 mmHg, as compared with less than 140 mmHg, did not reduce the rate of a composite of cardiovascular and renal events. Achieved SBP of 130-139 mmHg was associated with a decreased risk for the primary outcome in patients with DKD. Trial registration ClinicalTirals.gov Identifier: NCT02620306, registered December 3, 2015. ( https://clinicaltrials.gov/study/NCT02620306 ).